Numerical investigation on the transverse jet into a supersonic crossflow with different pressure ratios - Yanfeng Xiao; Huanhao Zhang; Zhihua Chen; Hui Zhang; Chun Zheng (Engineering Applications of Computational Fluid Mechanics, 2024)
The jet can be applied to the yaw control of a projectile, however, the complex interaction of the jet with the supersonic mainstream makes the flow field complex and yaw force unpredictable. To reveal the evolution of flow structures under different pressure ratios (PRs), or momentum flux ratios, a transverse sonic jet injected into a supersonic laminar crossflow has been studied numerically. Large-eddy simulations are employed to simulate the flow fields and evolution tendency of flow structures under different PRs of 10, 50, 100, 300, and 500. Our results show clearly the shock and flow structures of the jet interaction with crossflow under different PRs. Moreover, we find that, with the increase of PR, a larger upstream recirculation zone (RZ) and jet shock core appear, which accelerates the transformation of the bow shock (BoS) and the instability of the jet shear layer due to its stronger interaction with the crossflow. In addition, a high PR also accelerates RZ instability and produces a strong compressing effect on the major counter-rotating vortex pair in the jet flow, which makes the streamwise vortex tube stronger in the wake. These findings provide important information for applications of jet control of projectiles.